Country of origin matter to brand equity between two electronic giant companies of Japan and South Korea / Fatin Nabilah Abdullah - Abdullah, Fatin Nabilah (Faculty of Business and Management, 2014)
In January 2013, based on Interconnected Economies: Benefiting from Global Value Chains – Synthesis Report Organization, from Economic Co-operation and Development (OECD) Development Assistance Committee’s, stated that Asia are competing each other to build strong brand and set many records for economic and social achievement. In fact, on year 2014, International Data Corporation (IDC) Worldwide Quarterly Mobile Phone Tracker, vendors shipped a total volume of 1,004.2 million Smartphone’s worldwide for one billion units in a single year for the first time. The big picture shows huge gap between 2013 performance, where 284.4 million Smartphone’s has been shipped worldwide. This indicates an increment up to 24.2% compared to 55.1% of all mobile phone shipments in 2012. According to (GfK. News, 2014) GfK forecasts the global unit sales of LCD TVs to consumers grow 4 % to 217 million in 2013. Based on Forbes 2013, from Top 100 World’s Most Valuable Brands, it was reported SAMSUNG Electronics stands in the rank of 9 among 100 listed valuable brands, while Sony stands on rank of 80 in the same lists. It is an automatic augment the apparent of export oriented growth formula which makes some changes towards giant electronic market leader. This research focuses on rapid rise from South Korea electronics giant SAMSUNG and the slump business from Japan electronics giant, SONY. The current trajectory leads to growing inequality and falling consumption growth. Refers to root of the problem, researcher really interested to study on how SAMSUNG move so fast and SONY becomes dawdling in the market.